Legal Concept of the Fiscal State - Patsurkivskyy, Petro (European Journal of Law and Public Administration, 2019)
The article shows that the concept of the Fiscal State belongs to the categorical-conceptual apparatus of the etatist doctrine of tax law. It is assigned to one of the key roles in the apologetics of this doctrine, and therefore the methodological approaches of this doctrine can’t reliably reveal it. Thus, the authors of the article used the anthroposociocultural approach to the analysis of the legal concept of the Fiscal State. In particular, such components of this approach as historical and genetic methods in combination with the method of system-structural analysis. With their help, it was found that the historical and genetic origins of the legal construction of the "Fiscal State" date back to the late Antiquity. The article demonstrates that at that period took place the Late Antique Civilizational Revolution, which resulted in displacement of the human centered mentality of the population of Republican Rome by the etatistician mentality. As a consequence, the Ancient Roman Republic was transformed into the Ancient Roman Empire, the citizens of the Roman Republic became the subjects of the Roman Empire, and their public needs transformed into the needs of the Roman Empire. The last phenomenon became the quintessence of the Roman Redistributive Revolution, which was initiated by the Roman Emperor Octavian August and completed by Roman Emperor Diocletian. The most concentrated legal consequence of the aforementioned social transformations, as proved in the article, was the emergence of the Fiscal State and the initiation of the historical tradition of its tax law. The article concludes that the legal concept of the Fiscal State, as well as the phenomenon that gave rise to it, were proved by stable historical constructions. Even after two thousand years since their emergence as social facts, their fundamental values have remained unchanged. These include: the association of a Fiscal State with the Hegel`s "procession of God on Earth" as the highest social justice; the perception of this State as ontologically independently rooted in the being subject, which is the core of society; interpretation of the tax as an attribute of the Fiscal State; identification of the sovereignty of the Fiscal State with its tax sovereignty. Consequently, the Fiscal State considers itself as a subject of redistribution of GDP and national income.
Keywords: Fiscal State; tax as an attribute of a Fiscal State; tax sovereignty of the Fiscal State